PENGARUH HARGA, KUALITAS PRODUK, DAN CITRA MEREK TERHADAP KEPUASAN KONSUMEN MELALUI KEPUTUSAN PEMBELIAN DI PT BALI COKLAT JUNGLEGOLD BALI: PENGARUH HARGA, KUALITAS PRODUK, DAN CITRA MEREK TERHADAP KEPUASAN KONSUMEN MELALUI KEPUTUSAN PEMBELIAN DI PT BALI COKLAT JUNGLEGOLD BALI - Jaya, I Gede Bilva Rangga; Dewi, Ni Luh Prima Kemala (Journal Science Innovation and Technology (SINTECH), 2025)
This study aims to identify the characteristics of visitors to PT Bali Coklat Junglegold Bali and analyze the influence of price, product quality, and brand image on consumer satisfaction through purchase decision. This research employed a quantitative approach with Structural Equation Modeling–Partial Least Square (SEM-PLS). A sample of 100 respondents was selected using purposive sampling from visitors who had made repeated purchases. The results show that price, product quality, and brand image have a significant influence on purchase decision. Purchase decision also significantly affects consumer satisfaction. However, the mediation test indicates that purchase decision does not mediate the relationship between the independent variables and consumer satisfaction. These findings suggest that while these factors drive purchase decision, the indirect pathway does not significantly contribute to enhancing consumer satisfaction.